Ubiquitylation of BBSome is required for ciliary assembly and signaling. (6th February 2023) - Chiuso, Francesco; delle Donne, Rossella; Giamundo, Giuliana; Rinaldi, Laura; Borzacchiello, Domenica; Moraca, Federica; Intartaglia, Daniela; Iannucci, Rosa; Senatore, Emanuela; Lignitto, Luca; Garbi, Corrado; Conflitti, Paolo; et al.
Abstract: Bardet‐Biedl syndrome (BBS) is a ciliopathy characterized by retinal degeneration, obesity, renal abnormalities, postaxial polydactyly, and developmental defects. Genes mutated in BBS encode for components and regulators of the BBSome, an octameric complex that controls the trafficking of cargos and receptors within the primary cilium. Although both structure and function of the BBSome have been extensively studied, the impact of ubiquitin signaling on BBSome is largely unknown. We identify the E3 ubiquitin ligase PJA2 as a novel resident of the ciliary compartment and regulator of the BBSome. Upon GPCR‐cAMP stimulation, PJA2 ubiquitylates BBSome subunits. We demonstrate that ubiquitylation of BBS1 at lysine 143 increases the stability of the BBSome and promotes its binding to BBS3, an Arf‐like GTPase protein controlling the targeting of the BBSome to the ciliary membrane. Downregulation of PJA2 or expression of a ubiquitylation‐defective BBS1 mutant (BBS1 K143R ) affects the trafficking of G‐protein‐coupled receptors (GPCRs) and Shh‐dependent gene transcription. Expression of BBS1 K143R in vivo impairs cilium formation, embryonic development, and photoreceptors' morphogenesis, thus recapitulating the BBS phenotype in the medaka fish model. Synopsis: PJA2 is a novel resident of the ciliary compartment. Upon GPCR‐cAMP stimulation, PJA2 ubiquitylates BBSome subunits and controls the assembly and disassembly of BBSome at cilia. Defects in ubiquitylation may induce Bardet‐Biedl syndrome in medaka fish. E3 ubiquitin ligase PJA2 is a component of the ciliary compartment and interacts with subunits of the BBSome. GPCR‐cAMP stimulation induces PJA2‐mediated ubiquitylation of BBS1 and BBS2 and BBSome complex assembly. Downregulation of PJA2 or expression of a ubiquitylation‐defective BBS1 mutant (BBS1 K143R ) impairs the trafficking of G‐protein‐coupled receptors (GPCRs) and cilium formation. Expression of BBS1 K143R affects cilium formation, embryo development, and photoreceptor morphogenesis in the medaka fish model. Abstract : PJA2 is a novel resident of the ciliary compartment. Upon GPCR‐cAMP stimulation, PJA2 ubiquitylates BBSome subunits and controls the assembly and disassembly of BBSome at cilia. Defects in ubiquitylation may induce Bardet‐Biedl syndrome in medaka fish.